Pulmonary involvement in patients with hematological malignancies - Azoulay, Elie.; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
The number of patients treated for hematological malignancies is increasing steadily. To obtain the highest possible cure rates, aggressive treatments have been introduced, including high-dose chemotherapy, stem cell transplantation, and targeted therapies. As a result, overall and disease-free survival rates have improved substantially; however, this has been achieved at the price of life-threatening toxic and infectious complications that chiefly target the lung. This book provides clinicians caring for patients with hematological malignancies with detailed, up-to-date information on all relevant aspects of pulmonary involvement. Individual sections are devoted to epidemiology, diagnostic strategy, lung infections, non-infectious pulmonary involvement, and treatment, including decision making in patients with acute respiratory failure. Each of these sections contains a number of chapters, all written by leading international experts. In addition, the reader?s attention is drawn to important "pearls" relating to each condition.
Part 1: Preamble and Introduction -- Part 2: Epidemiology -- Part 3: Diagnostic Strategy In HM Patients -- Part 4: Lung Infections In Patients With HM -- Part 5: Noninfectious Pulmonary Involvement In Patients With HM -- Part 6: Treatment And Difficult Decisions In Patients With HM And ARF -- Part 7: Pearls That You Should Be Aware Of -- Part 8: POST FACE.
Electronic reproduction.
Keywords: Lungs -- Wounds and injuries; Cancer -- Treatment -- Complications; Electronic books